Do we need large Islamic rural banks? - Hendri, Zul; Wulandari, Eka; Sollehudin Shuib, Mohd (Economics, Finance, and Business Review, 2025)
This study aims to examine the non-linear impact of bank size on the profitability of Islamic rural banks (IRBs). Our study selected 90 banks situated on the Java Island. The study period spans 2018-2021, with quarterly data. Our study employs a dynamic panel regression using the GMM method. The results indicate that assets positively affect profitability. More importantly, the impact of an asset on profitability is inverted. In addition, these findings suggest that strong bank fundamentals, derived from high efficiency and high CAR, positively impact profitability. Several policy implications can be drawn from our findings. First, each bank must have a minimum of assets to achieve high profitability, around 187 billion. Second, to increase their profitability, Islamic rural banks must have adequate capital and a high operating efficiency.